George McCully journal - McCully, George, 1752-1793.
Manuscript copy of a journal (45 pages) kept by McCully pertaining to his journey (1783 June-July) from Pittsburgh, Pa., to Detroit, Mich., on an expedition headed by Ephraim Douglass to inform the Indians of that region that the Treaty of Paris would soon be signed. McCully documents meetings at "Delaware Town," a Delaware Indian settlement on the Sandusky River, Ohio, with Delaware chief Captain Pipe (also known as Hopocan or Kageshquanohel) as well as with members of the Shawnee and Wyandot tribes, captives living among the Indians, and Indian traders. McCully also describes meeting American Loyalist Mathew Elliott, of the Great Britain Indian Dept., Detroit, Mich. Includes note (1906, November 12) pertaining to the journal.
Handwritten transcript.
Army officer.
Collection material in English.
Published in Clarence M. Burton, "Ephraim Douglass and his Times, Including the Journal of George McCully and Various Letters of the Period," Magazine of History, Extra Number, no. 10 (1910), 39-49.
Keywords: Douglass, Ephraim, -- 1749?-1833.; Elliott, Matthew, -- approximately 1739-1814.; Hopocan, -- approximately 1725-1794.; Great Britain. -- 1783 September 3.; Great Britain. -- Indian Department; American loyalists; Delaware Indians; Indian captivities -- North America; Indian traders; Indians of North America -- Commerce; Indians of North America -- Ohio; Shawnee Indians; Wyandot Indians; Michigan -- Description and travel; Ohio -- Description and travel; Ohio -- History -- To 1787.; Pennsylvania -- Description and travel; Sandusky River Valley (Ohio) -- History; United States -- History -- Revolution, 1775-1783 -- Peace; Army officers